Lateral Trunk Surface as a new parameter to estimate live body weight by Visual Image Analysis - S. Terramoccia; S. Bartocci; G. Bianconi; P. Negretti (Italian Journal of Animal Science, 2010)
Live weight of 74 milking Mediterranean buffaloes (Bubalus bubalis L.) have been estimated by Visual Image Analysis. The total surface of lateral profile, tested in previous researches with viable result, was substituted by the measurement of the Lateral Trunk Surface (LTrS). The measurements were recorded by a camera equipped by a laser distance recorder and data were elaborated by a specific software. This parameter, eliminating the surface of neck, head and legs, that are less easily measurable, simplified and accelerated the procedure. Correlation between LTrS and live weight was r = 0.90 (P < 0.01). A significant equation (P < 0.01) was obtained from the recorded data of a random sample of 38 buffaloes. When the validation of the equation was tested on the other 36 subjects, the estimated live weight had a mean of 691.74 kg ± 68.55. This was corresponding to a 1.08% overestimation of the real weight.